Centering Acculturation as an Approach to Challenging the Fragility of Human Rights in Indonesia - Maksimus Regus (Journal of Southeast Asian Human Rights, 2022)
The degree of fulfillment of human rights differs from one situation to another, from one country to another. Although a country's constitution sets out the framework for protecting human rights, attacks on human rights at a practical level are visible. We can see that human rights are increasingly fragile. Specifically, Indonesia is experiencing a various kinds of human rights problems. For example, some minority groups such as the Ahmadiyya minority Group and Christians, routinely face discrimination and restrictions on human rights. This article discusses the concept of acculturation as an approach to challenging the fragility of human rights in Indonesia specifically and, more broadly, around the world. The author uses a critical analysis of previous academic studies to explore and elaborate on this discourse. Keywords: Acculturation, Human Rights, Minorities, State, UDHR, Indonesia